Analisis Faktor Risiko Kanker Serviks Pada Pasien Kanker Serviks Di Rsud Kabupaten Bekasi - Yuliandari, Irawati; Masluroh (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: to identify Cervical cancer is one of the most common cancers in women in the world. It is estimated that every year as many as 527,624 women are diagnosed with cervical cancer and 265,672 die from this disease To determine the relationship between age, age at marriage, number of sexual partners, number of births (parity), hereditary factors and use of oral contraceptives with the incidence of cervical cancer. Methods: This This study used a retrospective quantitative approach with a case-control research design. The population in this study were all cervical cancer patients treated at the Bekasi District Hospital for the period January-October 2023, namely 60 cases. Data collection was carried out through searching medical record data. Data were analyzed using the Chi-Square statistical test. Results: The results showed that there was a relationship between age and the incidence of cervical cancer (p-value: 0.000), there was a relationship between age at marriage and the incidence of cervical cancer (p-value: 0.000), there was a relationship between parity and the incidence of cervical cancer (p-value: 0.000), there is a relationship between the number of sexual partners and the incidence of cervical cancer (p-value: 0.000), there is a relationship between hereditary factors and the incidence of cervical cancer (p-value: 0.000), and there is a relationship between the use of oral contraceptives and the incidence of cervical cancer (p-value: 0.000) Conclusion: There is a relationship between age, age at marriage, number of sexual partners, number of births (parity), hereditary factors and use of oral contraceptives with the incidence of cervical cancer